Cutting temperatures during grinding - Milikić, Dragoje; Gostimirović, Marin (Journal of Production Engineering, 1994)
This article examines machining temperatures in machining from several important perspectives. The first aspect relates to the development and distribution of thermal energy during machining, including the definition of characteristic machining temperatures. The second aspect covers the problem of determining the temperature during grinding, both the characteristic machining temperatures and the overall temperature field. In this section, particular emphasis is placed on our own research into the development and application of our own methods for measuring temperature during surface grinding. The third aspect examines the influence of basic process parameters on the ability of cutting temperatures during grinding. In this context, the selection of cutting parameters for grinding is discussed. These cutting parameters should minimize the negative influence of the cutting temperature on the change in the oxide layer.